Assessing Rating Agencies' Ability to Predict Bank Bankruptcy – The Lace Financial Case. (20th June 2013) - SANTONI, ALESSANDRO; ARBIA, BARBARA
Abstract This paper responds to renewed interest in the following controversial question: do rating agencies have the ability to predict the risk of bank bankruptcy in a timely manner, and are they able to communicate it on time to the banking system? We tried to provide an answer to this question by checking when US banks that failed in 2009 were downgraded to Non‐Investment Grade (E). The database for this analysis consists of 116 US banks failing in 2009. The rating agency considered is Lace Financial Corporation. The study analyses the time series of ratings for the sample banks from the fourth quarter of 2005 to the date of bankruptcy and shows that over 72 per cent of the US banks that failed in 2009 had been downgraded to E in the fourth quarter prior to failure and 94 per cent had been rated E six months prior to bankruptcy. Empirical evidence from the Lace case does support the view that the Credit Rating Agency provides timely information to market participants.